2023
DOI: 10.1152/ajplung.00284.2022
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between elastin cross linking and alveolar wall rupture in human pulmonary emphysema

Abstract: Introduction: To better define the role of mechanical forces in pulmonary emphysema, we employed methods recently developed in our laboratory to identify microscopic level relationships between airspace size and elastin-specific desmosine and isodesmosine (DID) crosslinks in normal and emphysematous human lungs. Methods: Free DID in wet tissue (a biomarker for elastin degradation) and total DID in formalin-fixed, paraffin embedded (FFPE) tissue sections were measured using liquid chromatography-tandem mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We found that Dp16 mice showed a significant 1.3-fold increase in MLI, suggesting an increased alveolar airspace size comparable to mild-moderate emphysematous change in humans [ 50 ]. It is unclear whether increased MLI is associated with increased susceptibility to severe lung infection, although the links between acute exacerbations in COPD patients, bacterial infection, and worsening disease progression are well established [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that Dp16 mice showed a significant 1.3-fold increase in MLI, suggesting an increased alveolar airspace size comparable to mild-moderate emphysematous change in humans [ 50 ]. It is unclear whether increased MLI is associated with increased susceptibility to severe lung infection, although the links between acute exacerbations in COPD patients, bacterial infection, and worsening disease progression are well established [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a significant correlation between free lung DID and increasing airspace size, supporting the concept that these crosslinks may serve as a biomarker for airspace enlargement. This study was followed by measurements of free lung DID in both normal and emphysematous postmortem human lungs, which showed that elastin breakdown was greatly accelerated when mean airspace diameter exceeded 400 μm ( Figure 2 ) ( 29 ). The density of DID in lung tissue sections also increased markedly beyond 300 μm and leveled off at 400 μm.…”
Section: Introductionmentioning
confidence: 99%